The Role Of The Community And Village Empowerment Office Of West Sumatra Province In Increasing The Capacity Of BUMnag Management : Peran Dinas Pemberdayaan Masyarakat Dan Desa Provinsi Sumatera Barat Dalam Peningkatan Kapasitas Pengurus BUMnag - Bonavidiawati Zebua; Rizki Syafril (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to determine role West Sumatra Province Community and Village Empowerment Service in increasing the capacity administrators of village/Nagari-owned enterprises. This research was conducted using qualitative approach with descriptive methods. The results research concluded role Department of Empowerment and Community and Villages West Sumatra Province was to provide guidance and guidance to BUM Desa/Nagari. The activities carried out by PMD Service include carrying out coaching, technical guidance, socialization, data collection, supervision and monitoring in terms coaching for Village/Nagari BUMs as well as means of collaboration with third parties in supporting the development of Village/Nagari BUMs. Collaboration with 3rd parties The PMD Department collaborates with universities, for Village/Nagari BUM administrators who wish to continue their educational studies, campus will provide a 30% discount on tuition fees at Taman Siswa University and 25% at Darma Andalas University. There internship/KKN activities in cooperative studies at the Village/Nagari BUM office. In collaboration with Bank Nagari, there will be outreach to the directors of BUM Desa/Nagari regarding the provision of BUM Desa/Nagari business capital credit loans by Bank Nagari. Apart from that, the PMD Service also carries out assessments and appreciation in form of prizes for the best Village/Nagari BUMs every year as encouragement and motivation for Village/Nagari BUMs in West Sumatra. In increasing the capacity of Village/Nagari BUM administrators, there several obstacles or barriers to the PMD Service, including: lack of budget, so that the PMD Service limited in providing guidance and monitoring for Village/Nagari BUMs.